Handwriting isolated cursive letters in young children: Effect of the visual trace deletion. (August 2021) - Florence, Bara; Nathalie, Bonneton-Botté
Abstract: This study assesses the handwriting of isolated cursive letters in five-year-old children and the effect of a modification in visual feedback. Sixty-four children copied twelve cursive letters with an inking pen and a non-inking pen. Reducing visual feedback decreased the mean number of penlifts, and increased mean velocity and fluency. However, it increased the size of the letters (trajectory length) and reduced their quality. We suggest that processing visual feedback of the emerging visual trace may interrupt the fluency of the movement, while writing without seeing the trace may place greater emphasis on motor control and the use of somatosensory feedback. This study supplies reflection about sensory feedback and the moment when it should be provided in handwriting instruction. Practitioners should be aware that variation in the writing environment (surface, tools …) modifies sensory feedback and affects handwriting learning (gesture and outcome) in different manner. Highlights: Five-year-olds' letter handwriting is rapid but highly dysfluent. Writing with a non-inking pen impacts letter handwriting process and outcome. Reducing visual feedback increases velocity and fluency and decreases penlifts. Reducing visual feedback increases the size of the letters and lower their quality.